Brief communication: Improved measurement of ice layer density in seasonal snowpacks - Watts, Tom; Rutter, Nick; Toose, Peter; Derksen, Chris; Sandells, Melody; Woodward, John (The Cryosphere, 2016)
The microstructure and density of ice layers in snowpacks is poorly quantified. Here we present a new field method for measuring the density of ice layers caused by melt or rain-on-snow events. The method was used on 87 ice layer samples taken from natural and artificial ice layers in the Canadian Arctic and mid-latitudes. Mean measured ice layer density was 909 ± 28 kg m−3 with a standard deviation of 23 kg m−3, significantly higher than values typically used in the literature.